Combination of anti‐CD25 antibody and poly I:C treatment in pregnant NOD mice may be used as 'pregnancy‐related' type 1 diabetes model. Issue 9 (26th May 2022) - Shimada, Akira; Toda, Kyoko; Inoue, Ikuo; Yamada, Taketo; Oikawa, Yoichi
ABSTRACT: Aims/Introduction: Some women develop type 1 diabetes during pregnancy or immediately after delivery. However, the underlying pathophysiology remains largely unknown, probably because of the lack of a suitable animal model. In this study, we administered pregnant NOD mice with an anti‐CD25 antibody to reduce regulatory T cells along with poly I:C and examined the onset of diabetes. Materials and Methods: Anti‐CD25 antibody and poly I:C were intraperitoneally administered to mated female NOD mice. Mice delivered within 3 weeks after the treatment, and the onset of diabetes during pregnancy or within 6 weeks after delivery was examined. Some mice were killed 1 week after treatment, and their spleen and pancreas were excised to examine the expression levels of cytokines and for histological examination. Results: Half of the mice treated with anti‐CD25 antibody plus poly I:C developed diabetes, as compared with none of the poly I:C‐injected mice ( P  < 0.05). The ratios of interleukin‐18/forkhead box P3 and granzyme B/forkhead box P3 were higher in the pancreas of anti‐CD25 antibody plus poly I:C‐treated mice than in the pancreas of control mice. The insulitis score decreased in the pancreas of anti‐CD25 antibody plus poly I:C‐injected pregnant NOD mice. Conclusions: We describe the use of anti‐CD25 antibody to reduce regulatory T cells and poly I:C as a Toll‐like receptor 3 stimulator to mimic viral infection in a pregnant NOD mouse, which can be used as a model of 'pregnancy‐related' type 1 diabetes. Abstract : A system of anti‐CD25 antibody, to reduce regulatory T cells, plus poly I:C, as a TLR3 stimulator to mimic viral infection, in pregnant NOD mice can be used as a model of pregnancy‐related type 1 diabetes.